The Impact of Behavioral Integration of Tourism Administrations in Achieving The Quality of the Services Provided - A Survey Study in a Sample of Iraqi Tourism Companies - Ryam Abdul-Wahab Ahmed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Tourism companies increasingly prioritize service quality to remain competitive in a rapidly changing tourism environment. Specific Background: Behavioral integration within management teams, reflected in information exchange, cooperative behavior, and participation in decision making, is considered an important organizational process that supports coordinated managerial work. Knowledge Gap: However, limited empirical evidence exists regarding the relationship between behavioral integration and tourism service quality within Iraqi tourism companies. Aims: This study examines the relationship between behavioral integration of management teams and the quality of tourism services in Iraqi tourism companies operating in Baghdad. Results: Data were collected from 204 management team members through a questionnaire and analyzed using SPSS and AMOS. The findings indicate a statistically significant correlation between behavioral integration and tourism service quality (0.589). The dimensions of information exchange (0.472), cooperative behavior (0.410), and participation in decision making (0.461) also show significant relationships with service quality. Regression analysis confirms that behavioral integration contributes to tourism service quality with an effect coefficient of 0.686, while cooperative behavior shows the highest contribution among the dimensions. Novelty: The study provides empirical evidence linking managerial behavioral integration with tourism service quality in Iraqi tourism companies using quantitative analysis. Implications: These findings highlight the importance of strengthening cooperation, information sharing, and participatory decision processes within management teams to support the development of tourism service quality. Highlights:• Statistical Analysis Confirms a Significant Association Between Managerial Collaboration and Tourism Service Standards• Cooperative Practices Within Management Teams Demonstrate the Strongest Contribution Among Examined Dimensions• Evidence Derived From Survey Responses of 204 Managerial Staff in Baghdad Tourism Companies Keywords: Behavioral Integration, Tourism Service Quality, Information Exchange, Cooperative Behavior, Decision Making